Three new species and a new record of Smicridea McLachlan 1871 (Trichoptera: Hydropsychidae) from Minas Gerais state, Brazil - Rocha, Isabela Cristina; Dumas, Leandro Lourenço; Nessimian, Jorge Luiz (Zootaxa, 2016)
Three new species of Smicridea McLachlan 1871 are described and illustrated based on specimens collected in Parque Nacional da Serra da Canastra and its surrounding area, Minas Gerais state, southeastern Brazil. Smicridea (Rhyacophylax) necator sp. nov. possibly belongs to the S. (R.) dispar Group, but its placement in this group is weakly supported; S. (Smicridea) franciscana sp. nov. belongs to the S. (S.) nigripennis Group based on morphology of the phallus; S. (S.) sepala sp. nov. is a member of the S. (S.) fasciatella Group, also based on the morphology of the phallus. A new record of S. (S.) sattleri Denning & Sykora 1968 is provided for Minas Gerais state, Brazil.